Students Math Creative Thinking Skill - Jonni Sitorus (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2020)
This research aims at describing the ability and level of the student’s creative thinking. This is qualitative research. Operationally, this research was conducted with some steps, namely: giving a set of creative thinking test of 26 students to measure the ability and level of their creative thinking and choosing one student randomly from each student’s personality type to be interviewed to search their cognitive knowledge. The results show that every student has a creative thinking ability, but the level of creative thinking varies. The category of student’s creative thinking ability is “moderate or high.” The student’s creative thinking level is “very creative, creative, quite creative, or less creative.” The student’s cognitive knowledge is drawing, designing, ascertaining, dividing, reasoning, analogy, imagining, utilizing, solving, understanding, determining, mentioning, and using trial and error.